ROBOT FOLLOWER PEMBAWA INFUS PASIEN RUMAH SAKIT BERBASIS MIKROKONTROLER - ibnu sauki; Rian Ferdian (CHIPSET, 2022)
This study has the aim of designing a system that can carry intravenous fluids without human assistance, so it does not bother the patient in moving, this system is made of 2 components in the form of hardware where as hardware and software as software media, for hardware will use assistance from Arduino microcontroller, proximity sensor HC-SR04, DC motor, 11,1volt battery. which consists of 3 batteries, to be able to connect hardware, software or software is needed so that they can be connected to each other, the microcontroller used is an Arduino Uno, the system can run with input from the proximity sensor, which will read the position of the object that has been determined by the distance readings from the sensor, if the position of the object is known, the sensor will send input to the Arduino and process the input, after processing the Arduino will issue input which will be received by the L298N Driver where this driver regulates the rotational speed of the DC motor which will also rotate the wheels. so the robot can move and approach the object.